Effect of plant growth promoting bacteria on the phenology of the Amarilla maranganí quinoa cultivar (2022)
Bacteria associated with plant roots can generate different responses on the growth and development of plants which affect yield. For this reason, a test was conducted and aimed at evaluating the effects of plant growth promoting bacteria’s inoculation on the yield of the Amarilla Maranganí quinoa cultivar, using bacterial strains such as Bacillus macerans, Bacillus laterosporus, Bacillus licheniformis, Bacillus cereus, Actinobacillus, Pseudomonas aeruginosa, Consortia (a combination of the characterized bacteria), and DIPEL (Bacillus thuringensis var. Kurstaki). The study included the evaluation of the length of the plants and panicles as well as the number of inflorescences and seed production using a completely randomized experimental design. The results showed that the microorganisms had a large impact on plant growth. Actinobacillus increased the number of panicles while P. aeruginosa improved grain production. These results allowed us to confirm that the use of microorganisms favors the growth parameters of quinoa and allowed us to recognize the biological potential of growth promoting bacteria in this crop under conditions of poor water and nutrient availability.